2018
DOI: 10.1007/s10878-018-0316-4
|View full text |Cite
|
Sign up to set email alerts
|

On the weighted safe set problem on paths and cycles

Abstract: Let G be a graph, and let w be a positive real-valued weight function on V (G). For every subset X of V (G), let w(X) = v∈X w(v). A non-empty subset S ⊂ V (G) is a weighted safe set of (G, w) if, for every component C of the subgraph induced by S and every component D of G − S, we have w(C) ≥ w(D) whenever there is an edge between C and D. If the subgraph of G induced by a weighted safe set S is connected, then the set S is called a connected weighted safe set of (G, w). The weighted safe number s(G, w) and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Ehard and Rautenbach [14] presented a PTAS for the connected safe number of a weighted tree. Fujita et al [18] showed among other results that the problems can be solved in linear time for weighted cycles.…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Ehard and Rautenbach [14] presented a PTAS for the connected safe number of a weighted tree. Fujita et al [18] showed among other results that the problems can be solved in linear time for weighted cycles.…”
Section: Previous Workmentioning
confidence: 99%
“…That is, contrary to its name, having a small safe set could be unsafe for a network. Both the combinatorial and algorithmic aspects of the safe set problem have already been extensively studied [1,17,14,18].…”
Section: Introductionmentioning
confidence: 99%
“…For a vertex-weighted graph, Bapat et al [6] presented the weighted safe set problem by considering the graph as a community network. For further study about the weighted safe set, we refer to [7][8][9]. Furthermore, the study on safe set and weighted safe set was conducted by several authors.…”
Section: Introductionmentioning
confidence: 99%
“…They also constructed an efficient algorithm computing the safe number for a weighted path. Furthermore, Fujita et al [7] constructed a linear time algorithm computing the safe number for a weighted cycle. Ehard and Rautenbach [5] gave a polynomial-time approximation scheme (PTAS) for the connected safe number of a weighted tree.…”
Section: Introductionmentioning
confidence: 99%
“…Note that for every pair (G, w), s(G, w) ≤ cs(G, w) by their definitions. In [7], it was asked which pair (G, w) satisfies the equality and shown that every weighted cycle satisfies the equality. In this paper, we give a complete list of connected bipartite graphs G such that s(G, w) = cs(G, w) for every weight function w on V (G).…”
mentioning
confidence: 99%